Effect of doping on the mechanical properties of nonlinear GaSe crystals - Potekaev, Aleksandr I. 1951-; Andreev, Yury M. 1946-; Kokh, Konstantin A.; Svetlichnyi, Valerii A. (Russian metallurgy (Metally))
The effect of doping with sulfur, indium, tellurium, aluminum, erbium, and silver on the mechanical properties of nonlinear GaSe crystals grown by a modified Bridgman method with the rotation of a thermal field is studied. GaSe:S crystals have the best optical properties and GaSe:Al crystals have the highest microhardness. Under identical experimental conditions, we revealed an additive influence of double doping on the properties of GaSe: the crystals doped with sulfur and aluminum demonstrate the maximum efficiency of laser radiation frequency conversion and the maximum hardness. The increased hardness is supported by the appearing ability of the crystals to undergo cracking under the action of high-intensity radiation, which is characteristic of glass. @ 2016, Pleiades Publishing, Ltd.